JWST and ALMA Multiple-line Study in and around a Galaxy at z = 8.496: Optical to Far-Infrared Line Ratios and the Onset of an Outflow Promoting Ionizing Photon Escape - Seiji Fujimoto; Masami Ouchi; Kimihiko Nakajima; Yuichi Harikane; Yuki Isobe; Gabriel Brammer; Masamune Oguri; Clara Giménez-Arteaga; Kasper E. Heintz; Vasily Kokorev; Franz E. Bauer; Andrea Ferrara; et al. (The Astrophysical Journal, 2024)
We present Atacama Large Millimeter/submillimeter Array (ALMA) deep spectroscopy for a lensed galaxy at z _spec = 8.496 with $log(M_{star}/M_{\odot })\sim 7.8$ whose optical nebular lines and stellar continuum are detected by JWST/NIRSpec and NIRCam Early Release Observations in the field of SMACS J0723.3–7327. Our ALMA spectrum shows [O iii ] 88 μ m and [C ii ] 158 μ m line detections at 4.0 σ and 4.5 σ , respectively. The redshift and position of the [O iii ] line coincide with those of the JWST source, while the [C ii ] line is blueshifted by 90 km s ^−1 with a spatial offset of 0.″5 (≈0.5 kpc in the source plane) from the centroid of the JWST source. The NIRCam F444W image, including [O iii ] λ 5007 and H β line emission, spatially extends beyond the stellar components by a factor of >8. This indicates that the z = 8.5 galaxy has already experienced strong outflows as traced by extended [O iii ] λ 5007 and offset [C ii ] emission, which would promote ionizing photon escape and facilitate reionization. With careful slit-loss corrections and the removal of emission spatially outside the galaxy, we evaluate the [O iii ] 88 μ m/ λ 5007 line ratio, and derive the electron density n _e by photoionization modeling to be ${220}_{-130}^{+230}$ cm ^−3 , which is comparable with those of z ∼ 2–3 galaxies. We estimate an [O iii ] 88 μ m/[C ii ] 158 μ m line ratio in the galaxy of >4, as high as those of known z ∼ 6–9 galaxies. This high [O iii ] 88 μ m/[C ii ] 158 μ m line ratio is generally explained by the high n _e as well as the low metallicity ( ${Z}_{gas}/Z_{\odot }={0.04}_{-0.02}^{+0.02}$ ), high ionization parameter ( $logU\gt -2.27$ ), and low carbon-to-oxygen abundance ratio (log(C/O) = [−0.52: −0.24]) obtained from the JWST/NIRSpec data; further [C ii ] follow-up observations will constrain the covering fraction of photodissociation regions.